Pemberdayaan Mustahik Melalui Program Balai Ternak Baznas di Kabupaten Pidie Jaya Provinsi Aceh - Fatoni, Ahmad; Utami, Kurnia Dwi Sari (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The livestock center program is a form of community service, especially for mustahik in Pidie Jaya District, Aceh Province. Distribution of zakat funds to the productive BAZNAS livestock program with the target of turning mustahik into muzaki. Through a qualitative descriptive approach, the results show that the main empowerment activities of the BAZNAS livestock center program include empowering mustahik breeders through utilizing productive assets in the form of livestock and livestock production facilities, initiating and developing institutional business for breeders, building livestock production centers, and building product marketing networks. livestock and their derivatives. Keywords: Productive Zakat, Mustahik Empowerment, livestock hall